Hepatic glycogen levels in female rats submitted to aquatic therapy after muscle disuse - Jefferson Pacheco Amaral Fortes; Felipe Lima de Carvalho; Juliana Osório Alves; Marcia Maria Gonçalves Felinto Chaves; Mayara Rangel Araújo Carneiro; Vânia Marilande Ceccatto; Francisco Fleury Uchoa Santos Júnior; Karla Camila Lima de Souza (Desafio Singular, 2017)
The aim of the present study was to analyse the changes in liver glycogen content in rats subjected to aquatic therapy post-disuse of the paw. 32 wistar adult female rats were equally divided: Control (C), kept in the cage for two weeks without interventions; Disuse (D) had the right paw immobilized with hip extension, knee and plantar flexion for two weeks; Aquatic Therapy (AT) underwent aquatic therapy with increments of 3 minutes daily for two weeks, totalizing 36 minutes of training; Disused Aquatic Therapy (DTA) was first subjected to immobilization for two weeks and 24 hours after withdrawal of immobilization aquatic therapy was started for two more weeks, in same protocols of D and AT groups. At the end of the experiment, the animals were sacrificed, and tissues were dissected, weighed and stored. The liver tissues were referred analysis of glycogen content. It was observed that the blood glucose levels of the AT group (104 mg/dL) were different from the C group (86 mg/dL; p = 0.0213). Regarding hepatic glycogen, the D (2.35mg±0.07) and AT (2.73mg±0.07) groups had hepatic glycogen reduction by 22% and 15%, relative to C (2.51mg±0.03); p <0.0001). The DTA group presented no differences when compared to the control, suggesting the normalization of the finding. Muscle disuse by two weeks promoted changes in glycogen levels, however, two weeks after disuse condition, the aquatic therapy were able to correct the energetic reserve in liver.